The importance of negotiating good contracts - Karl P. Sauvant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
Complex contracts between governments and foreign investors, covering large-scale projects, define the long-term relationship between the parties. Negotiating such contracts is difficult under any circumstances, yet emerging markets negotiating with foreign investors often face an asymmetry of resources. This Perspective discusses how this asymmetry can be reduced through negotiations support. Also available in German (see below).
Keywords: 330